Analisis Faktor – Faktor Yang Mempengaruhi Pelaksanaan Tindak Lanjut Rekomendasi Hasil Pemeriksaan BPK Pada Kabupaten Pasaman - Rahmi Fauzia; Perengki Susanto (Jurnal Mirai Management, 2023)
This research aims to identify the factors hindering the completion of follow-up actions on the recommendations of the Supreme Audit Agency (Badan Pemeriksa Keuangan, BPK) in Pasaman Regency. A quantitative approach was utilized, and data were collected through questionnaires administered to key personnel involved in the follow-up activities in 37 government departments in Pasaman Regency.The findings revealed seven factors influencing the implementation of follow-up actions on BPK's recommendations, namely Technical and Coordination Factors, Leadership Factors, Civil Servants (ASN) and Non-Civil Servants and Third Parties Factors, Human Resources (HR) and Work Environment Factors, Non-Compliance Factors, Follow-Up Monitoring Factors, and Socialization Factors. The dominant hindering factor was identified as the Socialization Factor, with an average variable score of 4.55. In light of these findings, strategies to improve performance and enhance the completion of follow-up actions on BPK's recommendations were proposed. These include continuous monitoring and the support of the Inspectorate team in addressing findings and BPK's recommendations, revising and evaluating existing Standard Operating Procedures (SOPs) in the field, as well as conducting comprehensive socialization and clarification of regulations for all stakeholders involved. This research contributes valuable insights for Pasaman Regency and other local governments in strengthening their Internal Control Systems (ICS), particularly in financial management, and for the Inspectorate to optimize their role in facilitating follow-up actions. Future studies should consider expanding the theoretical framework to better comprehend the influence of identified factors in the follow-up process. The conclusion and recommendations from this study are expected to be beneficial for all stakeholders involved in completing follow-up actions on BPK's recommendations in Pasaman Regency and serve as a foundation for further research in this area. Keywords: Strategic Management, BPK, POAC, Hindering Factors, Local Government